‘Pure’ Constructional Apraxia—A Cognitive Analysis of a Single Case - Luigi Trojano; Dario Grossi (Behavioural Neurology)
We report on a patient affected by selective drawing disabilities. The patient could correctly reproduce and draw simple geometric figures on request, but when he tried to reproduce more complex drawings or to draw common objects he performed very poorly. To identify the cognitive impairment in this patient, we adopted two test batteries based on recent information-processing models of drawing. Results showed that the patient’s drawing disabilities were independent of visuo-perceptual and executive impairments. These findings support recent cognitive models of drawing abilities: some intermediate stages of drawing exist at which information is processed to prepare and guide motor output, and which may be selectively disrupted after discrete cerebral lesions.